2011
DOI: 10.1128/jb.01052-10
|View full text |Cite
|
Sign up to set email alerts
|

Type I Signal Peptidase and Protein Secretion inStaphylococcus epidermidis

Abstract: Bacterial protein secretion is a highly orchestrated process that is essential for infection and virulence. Despite extensive efforts to predict or experimentally detect proteins that are secreted, the characterization of the bacterial secretome has remained challenging. A central event in protein secretion is the type I signal peptidase (SPase)-mediated cleavage of the N-terminal signal peptide that targets a protein for secretion via the general secretory pathway, and the arylomycins are a class of natural p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 72 publications
(87 reference statements)
3
34
1
Order By: Relevance
“…This result indicated that the cleavage that releases the sensor domain occurs between amino acids Gly-331 and Glu-332. This type of processing was recently shown to be due to the action of type I signal peptidase in Staphylococcus epidermidis (27). BlaR1 from S. epidermidis has a high probability type I signal peptidase recognition sequence just to the C-terminal side of the last predicted transmembrane helix, and cleavage after Gly-331 was predicted for BlaR1 from S. epidermidis.…”
Section: Resultsmentioning
confidence: 96%
“…This result indicated that the cleavage that releases the sensor domain occurs between amino acids Gly-331 and Glu-332. This type of processing was recently shown to be due to the action of type I signal peptidase in Staphylococcus epidermidis (27). BlaR1 from S. epidermidis has a high probability type I signal peptidase recognition sequence just to the C-terminal side of the last predicted transmembrane helix, and cleavage after Gly-331 was predicted for BlaR1 from S. epidermidis.…”
Section: Resultsmentioning
confidence: 96%
“…Similarly, processed forms of LtaS-type enzymes were found in the supernatants of L. monocytogenes, Bacillus anthracis, Bacillus cereus, Bacillus thuringiensis, and Staphylococcus epidermidis cultures (2,18,37,44). In all cases where the cleavage site of LtaS-type enzymes has been mapped, it occurs after an Ala-X-Ala motif, and the location of the motif within the protein is conserved in LtaStype enzymes.…”
mentioning
confidence: 95%
“…A proteomic study of B. subtilis showed that processing of the LtaS-type enzyme YfnI was diminished in the combined absence of two signal peptidases, SipT and SipV (1). More recently, it was reported that addition of the signal peptidasespecific inhibitor arylomycin to S. epidermidis cultures led to a reduction in the amount of a processed LtaS fragment in the culture supernatant (37). However, in the same study, an alternative LtaS processing site, located after residues 171 AlaPhe-Ala 173 and closer to the 5TM domain, was proposed based on the results of a computer prediction program (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ternal signal peptides in a few polytopic membrane proteins (8,12,70,118,147). E. coli SPI is the best-studied signal peptidase in this family.…”
Section: Signal Peptidase Imentioning
confidence: 99%